Mycobacterium malmoense bacteremia in two AIDS patients. - Fakih, M (1996)
We report two cases of Mycobacterium malmoense bacteremia in two patients with AIDS. These are the first reported cases of disseminated M. malmoense in human immunodeficiency virus patients occurring in the United States. This slow-growing organism can cause invasive disease mimicking Mycobacterium avium complex infection; recognition and identification of this organism by mycobacteriology laboratories are essential for appropriate diagnosis and therapy of disseminated disease.